Beo dalam Sistem Sosial Masyarakat Manggarai di Satarara - Hambur, Liventinus; Suarsana, I Nyoman; Murniasih, Anak Agung Ayu (Sunari Penjor : Jurnal of Anthropology, 2023)
The people of Satarara Hamlet in carrying out their daily lives are based on the social system that exists in society, so that with the existence of a system, people can easily carry out everything in social life. This research was conducted to find out the elements that make up beo/golo are, and beo function in the social system of society. The method used in this research is qualitative by using structural functionalism theory and systems theory. This study uses several techniques in obtaining data, namely observation, interviews, and literature study. Based on the results of the study, the social system in society is a system formed because of the actions and interactions carried out by the community to achieve a common goal. As for some of the elements in forming a parrot, namely: Mbaru bate ka'eng, Natas bate Labar, Uma bate duat, Wae bate teku, and Compang bate dari. The system that is formed usually makes it easier for the community to carry out daily activities, be it in the form of deliberation, family activities, or mutual cooperation (dodo).